Comparative study of the antioxidant activities of 'barako' coffees - De Torres, Lexa Lyn M.
ABSTRACT While the popularity of coffee stays at peak and antioxidants become its biggest selling point, ?Barako‟ coffee (C. liberica) remains to be at the periphery in the coffee market. Hence, this study aimed to investigate the antioxidant level of Barako coffee compared to other coffee varieties grown in the Philippines. Aqueous extract of C. liberica was prepared using a conventional drip coffee maker and its antioxidant activity was investigated in comparison with other Philippine coffee varieties (C. excelsa, C. arabica and C. robusta). Total phenolic content was determined by Folin-Ciocalteu assay while antioxidant activity was investigated by measuring its DPPH radical scavenging capacity and reducing power. Results of the experiment showed that ?Barako‟ coffee (i) contains 3000 ± 100 mg GAE/L which is significantly higher (P<0.05) than the values obtained from C. excelsa and comparable to C. arabica; (ii) has 50 % inhibitory concentration (IC50) value of 264.60 ± 8.90 mg coffee/L extract obtained using the DPPH assay which showed that Liberica coffee has higher radical scavenging capacity than C. excelsa; and (iii) has IC50 value of 985.52 ± 112 mg coffee/L extract obtained from the reducing power assay which suggested that Liberica coffee has the highest reducing capacity among the Philippine coffee varieties. Hence, ?Barako‟ coffee was demonstrated to contain a remarkable level of antioxidant which is greater than those present in other Philippine coffee varieties considered as more commercially important. This implies that, if supported by future studies, ?Barako‟ coffee could claim its higher antioxidant properties in improving its underutilized status.